Emergency Department Visits Related to Inflammatory Bowel Disease. Issue 3 (September 2015) - Pant, Chaitanya; Deshpande, Abhishek; Fraga-Lovejoy, Camilla; O'Connor, Judith; Gilroy, Richard; Olyaee, Mojtaba
<x xml:space="preserve">Abstract</x> ABSTRACT We analyzed a national US database to study the presentation of children with inflammatory bowel disease (IBD) to the emergency department (ED). Our results indicate that from 2006 to 2010, there was a significant increase in the number of ED visits related to children with IBD accompanied by a contemporaneous decline in the rate of hospitalization that followed these ED visits. Earlier published results have highlighted an increased overall rate of hospitalizations in the United States related to children with IBD. In this context, our results support the evidence for an increased prevalence of pediatric IBD in the United States in recent years.